Understanding the business process of reactive maintenance projects - Ali, Kherun Nita; Ming Sun, Ming Sun; Aouad, Ghassan; Raja Mazlan, Raja Marzyani; Mustapa, Fara Diva (2006)
This paper presents the analysis of the existing business process in reactive maintenance projects including the information and communication technology that supports the process. All information reported in this research is mainly primary data gathered from interviews with the parties that are involved in the process. The analysis consists of identification of the parties involved, understanding the business process, understanding the information and communication technology used in the process and identification of problems within the process. The research reveals several existing deficiencies with RM projects which require some measures of improvement i.e. poor communication between different parties; lack of knowledge sharing; and poor quality of information, which often lead to longer time taken to fix a problem and incurs higher cost.